Social Engineering Through Street Vendor Licensing in Urban Informal Economy Governance - Rayani Saragih; Jefri Jefri; Maslon Hutabalian (Law Development Journal, 2026)
This study aims to analyze street vendor licensing as an instrument of social engineering in urban informal economy governance and to assess its effectiveness in supporting urban spatial order while protecting the right to a decent livelihood for informal economic actors. The research employed a normative legal research method using statutory, conceptual, and analytical approaches. Secondary data were collected from legal regulations, policy documents, court decisions, and recent scientific literature related to informal economy governance and urban spatial planning. The novelty of this research lies in its examination of street vendor licensing not merely as an administrative regulatory mechanism, but as a social engineering instrument capable of transforming the relationship between the state, urban space governance, and informal economic actors. Unlike previous studies that primarily focus on enforcement and public order dimensions, this study emphasizes the empowerment-oriented function of licensing within the framework of constitutional economic rights and inclusive urban governance. The results indicate that the Indonesian legal framework has normatively provided constitutional and juridical recognition for the protection and empowerment of street vendors. However, in practice, licensing policies are still predominantly implemented as instruments of administrative control and spatial discipline rather than mechanisms for economic integration and social protection. The study further finds that street vendor licensing can function effectively as an instrument of social engineering when implemented through participatory, transparent, inclusive, and empowerment-based approaches. Based on the research, it is concluded that a paradigm shift from control-oriented governance toward empowerment-oriented governance is essential to ensure that street vendor licensing contributes to orderly urban spatial planning and the fulfillment of the right to a decent livelihood.